Pengaruh Dukungan Sosial terhadap Penyesuaian Diri Taruna Tingkat Pertama Jalur Mandiri di ATKP Makassar - Erna W, Agnes (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2018)
The purpose of the study is to determine of social support on Self Adjustment at first grade cadet of jalur mandiri of CASEA Makassar. The population of this staudy is the first-grade cadets of self-funding class. Sample amounted to 48 cadets. The sampling technique used proportional random sampling technique. Method of data retrieval using scale of social support and scale of self adjustment with likert scale modification. analysis using simple regression analysis. The results of this study have shown that the variables (X) social support significantly influence the variables (Y) self adjustment in cadet on jalur mandiri CASEA Makassar.This is shown from the results of correlation analysis of 0, 677. The coefficient of determination in this study amounted to 0.458 means social support affect the adjustment of 45.8% while the remaining 54.2% influenced by other factors that do not exist in this study. From result of t test have shown that thitung of Social support is 5,892 which is bigger than the value ttabel 1,682. Thitung > ttabel (5,892>1,682) then H1 accepted. This means that free variables of social support have a positive and significant effect on self adjustment variable